Evolution of the absorption of heavy metals in function of nutrients - Szaniszló, Albert; Demény, Krisztina (COLUMELLA – Journal of Agricultural and Environmental Sciences, 2018)
The condition of an eco-system greatly depends on the different biotic and abiotic factors. The area along the river “Tisza” is highly imperiled by random appearance of heavy metal pollutants originated from mining accidents or other sources. Heavy metals are dangerous because of the bioaccumulation and they could be toxic or poisonous even at low concentration. The aim of our research was to test the reaction of a simplified soil-plant pot experiment, consists of garden cress (Lepidium sativum) for metal pollution close to the sanitary limiting value. Garden cress is considered one of the most important agricultural vegetables and its short reaction time for various treatments makes this plant ideal object of eco-toxicological tests. Based on the results it is realistic assumption to expect decrease the above-mentioned flexibility character. Garden cress (Lepidium sativum) was chosen as a test plant to simulate the accessible pollutant uptake. Additionally, Lepidium sativum is a possible carrier of heavy metals in food chain, since it is a many-sided green vegetable consumed by humans and animals as well. The present study is undertaken to examine the level of accumulation as it is modified by a plant, if the plant growing up under other conditions. It appears how for each factor as in mobilizing heavy metals, the plant laboratory water will affect the special nutrient solution or soil pollution. Responsive changes are relevant for all of the different conditions relevant for mobile heavy metals. The accumulation levels may undergo variations in function of them. In the present study, such change is characterized by the cress garden.